Water Economy Through Matching Plant Root Elongation to Mediterranean Landscapes - Chysanthi Chimona; Sophia Rhizopoulou (World Journal of Research and Review, 2017)
Young plants of Ceratonia siliqua L., Myrtus communis L., Nerium oleander L., Rosmarinus officinalis L., Ligustrum japonicum Thunb. and Pittosporum tobira (Thunb.) Aiton were grown in long tubes as well in rhizotrons. After a period of acclimation to the conditions of the experimental construction under normal watering conditions, some plants were watered whereas other plants remained unwatered for a period of one month. During the studying period the plants have been observed and regular measurements of roots and above ground parts development were taken. The results show the resistance of the Mediterranean plants (C. siliqua, M. communis, N. oleander) to water deficit in comparison to plants that are often used in parks and urban horticulture (L. japonicum, P. tobira), whereas R. officinalis shows an intermediate stage of endurance to drought.